IMPLEMENTASI PERATURAN DERAH NOMOR 14 TAHUN 2010 DI DINAS PERHUBUNGAN, KEBUDAYAAN, DAN PARIWISATA KABUPATEN PONTIANAK - Dwi Kusumawardani E.42009010 (FISIP Universitas Tanjungpura Pontianak, 2013)
This paper is intended to yield a recommendation the implementation policy terminal retribution. The tittle of this paper was appointed based on existing problems, due the target of realization terminal retribution tax was not fulfill the estimate target of realization in every year. This research used qualitative research model. location of research sites in Pontianak District are Mempawah Terminal, Sungai Pinyuh Terminal, and Jungkat Terminal.The conclusions of this research are the implementor still lack socialization in order to the retribution object understand contents of regulation local clearly, still lack of human resources as retibution collectors, attitude of implementor still less of honest to collected the retribution, and there is no SOPS (Standard Operating Procedures). For recommendation the implementation of terminal retribution can be providing insight the contents of local regulation clearly in order that retribution collector do not collect unclear fare with that regulation local, human resources need added especially collector retribution officer, implementation in the field can be improved by giving rewards to officer. Key words : Terminal Retribution, Communication, Resources, Disposition, bureaucratic structure